Protocol for the simultaneous activation and lentiviral transduction of primary human T cells with artificial T cell receptors - Jordan Yong Ming Tan; Jia Chi Tan; Chuqi Wang; Ling Wu; Nicholas R.J. Gascoigne; Shruti Bhatt (STAR Protocols)
Summary: T cell-based therapies hold immense promise, but their production remains time-consuming and technically complex. Here, we present a protocol that streamlines the activation and lentiviral transduction of primary human T cells with artificial receptors. We describe steps for T cell isolation, lentivirus production, and the simultaneous activation/transduction of T cells. By eliminating magnetic T cell activation beads, sequential steps, and lengthy spinoculation, this protocol significantly enhances efficiency, scalability, and accessibility for research and therapeutic applications. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.